2018
DOI: 10.3892/ijo.2018.4538
|View full text |Cite
|
Sign up to set email alerts
|

CDCA3 mediates p21-dependent proliferation by regulating E2F1 expression in colorectal cancer

Abstract: Dysregulated cell cycle progression serves a crucial role in tumor development. Cell division cycle- associated 3 (CDCA3) is considered a trigger of mitotic entry; it is an important part of the S phase kinase-associated protein 1/Cullin/F-box ubiquitin ligase complex and mediates the destruction of mitosis-inhibitory kinase wee1. However, little is known about the role of CDCA3 in cancer, particularly colorectal cancer (CRC). The present study aimed to explore the biological and clinical significance of CDCA3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 33 publications
1
50
0
Order By: Relevance
“…Some bioinformatics analysis had suggested that CDCA3 contributed to the pathological process in several cancers, including breast cancer [25], bladder cancer [23] and liver cancer [26,27]. Previous studies had shown that the functional loss of CDCA3 might block the transition from the GO/G1 phase of BGC823, H1 and Sa3 cells [2,[7][8][9]. Three retrospectively cohort studies had indicated that CDCA5 was overexpressed in HCC [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some bioinformatics analysis had suggested that CDCA3 contributed to the pathological process in several cancers, including breast cancer [25], bladder cancer [23] and liver cancer [26,27]. Previous studies had shown that the functional loss of CDCA3 might block the transition from the GO/G1 phase of BGC823, H1 and Sa3 cells [2,[7][8][9]. Three retrospectively cohort studies had indicated that CDCA5 was overexpressed in HCC [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Recently some researchers revealed that CDCAs might contribute to the cancer progression. Previous studies had shown that some members of this gene family might be up-regulated in breast cancer, lung adenocarcinoma and pancreatic adenocarcinoma [5][6][7][8][9][10][11][12][13][14][15][16]. And high expression levels of these genes were identified as poorly predictive factors of survival in these cancers [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…CDCA3 controls the G1 phase [30], which acts as one of the prognostic genes for hepatocellular carcinoma (HCC) [31] and is also involved in LC cell proliferation, migration, invasion, and apoptosis [30], as well as CRC cell proliferation [32]. Moreover, it has been reported that CDCA3 expression is related to prognosis for bladder cancer cases [33] and luminal A breast cancer [34].…”
Section: Discussionmentioning
confidence: 99%
“…Previous data analysis indicated that CDCA3 showed on average > 100 -fold overexpression in BC compared with normal tissue 34 . Meantime, CDCA3 has been demonstrated to be expressed in liver cancer, oral squamous cell carcinoma tissue, non-small cell lung cancer and prostate cancer cells 35 . However, the role of CDCA3 in malignant tumors remains unclear.…”
Section: Analysis Of Core Genes By the Kaplan Meier Plotter And Gepiamentioning
confidence: 99%